Analisis Strategi Pemasaran Produk Oxygen PT Moratelindo Jakarta - Tidar Ramdan Sanjaya; Hapsari Widayani (Duconomics Sci-meet (Education & Economics Science Meet), 2021)
The development of internet business has experienced a fairly tight competition where between companies compete with each other to attract customers to use their products with various products and services. PT Moratelindo is one of the internet service providers in Jakarta. The purpose in this research is to find out the marketing strategies used have been efficient and effective. The method used is qualitative with a descriptive approach. Data collection techniques by means of observation, interview, documentation, and recording. The result of the analysis using marketing mix, Oxygen product is a quality internet service product with 100% service using fiber optic cable.  PT Moratelindo has a 7P mix that can see opportunities and attract the market to use Oxygen products. Proven from 2018 Oxygen Products have increased every year with an average of 18,148 new customers every year or 1,512 new customers every month. While the highest product achievement is the stream package with a total of 30,410 customers from 2018 – 2019. Based on the results of the data analysis shows that Oxygen products are in a stable phase and the strategies used efficiently and effectively.